Design of highly efficient g-C3N4-based metal monoatom catalysts by two extra-NM1 atoms: density functional theory simulations. Issue 19 (7th May 2021) - Chen, Miaogen; Chang, Wenya; Shi, Yaxin; Liu, Wei; Li, Can
Abstract : Volcano activity relationships between the η OER with solvation effect and ε d values. Abstract : Graphitic carbon nitride (g-C3 N4 ) is recognized as a favorable substrate for monoatom catalysts due to its uniform nanoholes for anchoring metal monoatoms, while the oxygen evolution reaction (OER) overpotential ( η OER ) values of g-C3 N4 -based metal monoatom catalysts are still large. To reduce the η OER values, a class of novel TM1 NM1 NM1 /g-C3 N4 was designed via density functional theory simulations, where TM1 = Fe1, Co1 or Ni1 and NM1 = C1, N1 or O1 . Contributing by two extra-NM1 atoms, the OER catalytic activities of these materials were effectively improved owing to the shortened TM1 –NM bonds and weakened chemical activity of TM1 atoms. Based on the volcano activity relationship between the theoretical overpotential ( η OER ) and d band center of the TM1 atom ( ε d ), the chemical activity of TM1 atoms needs to be adjusted to a suitable magnitude ( ε d near −4.883 eV) for a good catalytic activity. The designed Fe1 C1 O1 /g-C3 N4 with the ε d of −4.893 eV exhibited an excellent OER catalytic activity of η OER = 0.219 V. This strategy was applied to devise the reaction active sites and highly efficient catalysts by adjusting the chemical activity of the TM1 atom with suitable extra-NM1 atoms.